SELF-NANO EMULSIFYING DRUG DELIVERY SYSTEM OF EFAVIRENZ: FORMULATION, IN VITRO EVALUATION AND CHARACTERIZATION - PAMU SANDHYA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of this study was to preparation and evaluation of efavirenz (EFV) to enhance its solubility and dissolution rate by self-emulsifying drug delivery system. Methods: EFV self-emulsifying drug delivery systems (SNEDDS) were formulated using different oils, surfactant, and co-surfactant. Peceol, Tween 20, and Capmul MCM were used as oil, surfactant, and co-surfactant, respectively, followed by the evaluation by the performance of different tests such as visual observation, solubility studies, thermodynamic stability study, transmittance studies, drug content, and in-vitro release study. Results: Fourier-transform infrared studies revealed negligible drug and polymer interaction. From the phase diagram, it was observed that self-emulsifying region was enhanced with increasing surfactant and co-surfactant concentrations with oil. F13 was selected as optimized formulation on the basis of physicochemical parameters, particle size, and in-vitro dissolution studies with the release of 98.39±5.10% drug in 1 hour. The optimized formulation size was found to be 156.7 nm as mean droplet size and Z-Average of 808.6 nm with -18.3 mV as zeta potential. Conclusion: The study demonstrated that SNEDDS was a promising strategy to enhance the dissolution rate of EFV by improving solubility.